Pengurusan Fasiliti Dalam Penyelenggaraan Bangunan:Amalan Kualiti, Keselamatan dan Kesihatan - Hafizi Zakaria; Kadir Arifin; Shaharuddin Ahmad; Kadaruddin Aiyub; Zahedi Fisal (Journal of Techno-Social, 2011)
Malaysia is a speedy developing country and now struggling to become a developed country with a first class infrastructural network. Towards the vision, various developments have been well planned especially in building construction sectors in order to fulfill the need of society and an organization. In the hasty stream of building construction whether government, private or personal building, the facilities management planning should not be neglected. The planning of building and facilities management before, during and after a building creation must be parallel to maintain the initial condition of the building and to ensure the surrounding of the building is always in good quality, safe and healthy to all occupants or visitors of the building. Practically the construction management only focuses on before and after building construction. Otherwise the facilities management should focus on three levels that are before, during and after construction. Nowadays, many issues reflected to quality, safety and health originated from the weakness of facilities management especially building maintenance aspect such as impairment, fire, collapse, failure compliance of law and so on. Such events will threat the safety and health of the occupants and visitors of buildings. So, the quality, safety and health practices are two essential elements in building maintenance to ensure that all occupants always comfortable, safe and healthy during occupation of a building. This paper discussed a few factors that should be considered by facilities management organization to maintain a good level of quality, safe and healthy of a building. Some of the factors are developing objective, policy and strategy; implementation of planning; providing budget; procedure development, regulation and standard compliance; and human resources.